Lenininės nacionalinės politikos atspindžiai tarybinėje bibliotekininkystėje - Sinkevičius, Klemensas (Knygotyra, 1972)
The government of tsarist Russia had pursued an anti-national policy of “enlightenment”. In the beginning of the 20th century library network in Russia was very small. In many national regions the stocks of public libraries held less than one book per a 100 inhabitants.V. Lenin, Marxists-Leninists advanced the slogan of equality among peoples, fought for political, economic and cultural development of all the nations and nationalities of the country. The victory of the Great October Socialist Revolution determined the realization of the principles of Leninist national policy.Two tendencies may be distinguished in the history of the development of libraries in the Soviet Union.(1) The librarianship is developed in each national republic, taking into consideration the tenor of life of the population, traditions, plans of economic and cultural development and so on. During a historically short time a broad network of various types of libraries has been created, abundant library holdings have been collected, including the national literature stocks; national staff has been trained, republican centres of librarianship have been established: national libraries, institutions of national bibliography – Book Chambers etc. In this process the libraries of more developed republics rendered a considerable material assistance and gave advice to the libraries of less developed republics.(2) An assimilation and unification of the library work in different republics have been taking place, All-Union administrative and scientific-methodical centres of management have been established, important documents such as regulations, statutes, rules, and other normative documentation have been worked out.The data of recent years show that any Soviet Republic leaves behind developed capitalist countries by the number of books per head of population. For example, the rate of books in the stocks of public libraries of Soviet Lithuania is 5.7, while in Sweden – 2.6, in Norway – 2.5, in Finland – 2.2, in England – 1.9, in Netherlands – 0.7, in West Germany – 0.5, etc.The conditions of modern scientific-technical revolution raise new tasks for the libraries of our country in the sphere of cultural mass activities and scientific information. The solution of these problems envisages a further development of librarianship in national republics, the improvement of coordination and unification of work of the libraries in our country and expansion of the system of business information.The Leninist national policy serves as a firm basis for using all our available theoretical, methodical and material potential in order to solve the tasks of the further development of librarianship in our country.